Accounting information system and organizational performance of selected home-grown coffee shops in Iloilo City - Inodeo, Urs Martin N.; Laserna, Shaira Paula A.; Lusica, Metchie Anne L.; Suyom, Steve John B.; Villaver, Kilsey Liandee B.
Coffee shops have been notable for providing satisfaction to Filipinos' cravings. During the onslaught of Coronavirus-19 (COVID-19), several micro-,small-, medium-sized coffee shops in Iloilo City were affected leading to their foreclosure and liquidation. However, some selected home-grown coffee shops have survived the economic crises. Thus, this study aimed to discuss the quality of accounting information system (AIS) and the organizational performance of selected coffee shops; describe how the users of the AIS of home-grown coffee shops in Iloilo City perceive the effectiveness of using the AIS on organizational performance; and formulate recommendations on how to improve their organizational performance. With the use of a qualitative approach, primary data was obtained through face-to-face interviews using a semi-structured interview guide. Further, purposive sampling was employed, and only personnel-in-charge in the company's AIS and operations were interviewed. The results reveal that the selected home-grown coffee shops in Iloilo City have a high-quality accounting information system and high level of organization. Moreover, AIS provides relevant information for decision making, and produces accurate, complete, and timely information for effective decision making. The selected coffeeshops also encountered technical problems with regards to their AIS, however these coffee shops still perceive the AIS useful and beneficial to their organizational performance. Further, the businesses continue to improve their organizational performance by using various strategies, which is aided by a high-quality AIS. The study recommends that the selected home-grown coffee shops provide training to their employees, invest into the integration of their AIS as a whole, and utilize the management reports effectively to further improve the quality of their current AIS.